Developmental basis of SHH medulloblastoma heterogeneity - Gold, Maxwell; Ong, Winnie; Masteller, Andrew M.; Ghasemi, David R.; Galindo, Julie Anne; Park, Noel R.; Huynh, Nhan C.; Donde, Aneesh; Pister, Veronika; Saurez, Raul A.; Vladoiu, Maria C.; Hwang, Grace H.; et al. (Nature Communications, 2024)
Many genes that drive normal cellular development also contribute to oncogenesis. Medulloblastoma (MB) tumors likely arise from neuronal progenitors in the cerebellum, and we hypothesized that the heterogeneity observed in MBs with sonic hedgehog (SHH) activation could be due to differences in developmental pathways. To investigate this question, here we perform single-nucleus RNA sequencing on highly differentiated SHH MBs with extensively nodular histology and observed malignant cells resembling each stage of canonical granule neuron development. Through innovative computational approaches, we connect these results to published datasets and find that some established molecular subtypes of SHH MB appear arrested at different developmental stages. Additionally, using multiplexed proteomic imaging and MALDI imaging mass spectrometry, we identify distinct histological and metabolic profiles for highly differentiated tumors. Our approaches are applicable to understanding the interplay between heterogeneity and differentiation in other cancers and can provide important insights for the design of targeted therapies.